Ilmuan Wanita dan Diskursus Sains (Ilmu Pengetahuan) - Suryadilaga, Muhammad Alfatih (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
According to current research, the European commission reports that this year the number of women who receive a PhD (doctorate) reaches 40% or even more for